Modern indigenous culture [videorecording] (Australia : Video Education Australasia, 2008)
This program is a comprehensive, sensitive and accessible examination of modern indigenous culture and identity. Like everything in society, Aboriginal culture has the right to reinvent and transform itself and still maintain its authenticity and originality within a cultural context. Aboriginal culture is not frozen intime and Aboriginal people in contemporary times still have a dynamic reltionsip to their Dreaming. This program meets a variety of indigenous Australians and witnesses their expressions in art and achievements in sport which still maintain all the integrity, authentically and connectedness to a culture which continues to survice a barrage of external cultural influences.